Penyuluhan Tentang Kesehatan Reproduksi Terhadap Sikap Menghadapi Menopause - Endang Khoirunnisa; Rochayati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2016)
Background: Along with increasing age, many processes of development and growth in humans. The changes aremost common in women because of the aging process called pre-menopausal phase. Three out of ten women aged40-50 years old in the village Awu-awu, Ngombol, Purworejo said irregular menstruation, two women said regularmenstrual but the blood loss was reduced and they do not know the process they are experiencing is physiological.Objective: To determine the effect of counseling on reproductive health to the attitude faced of menopause inwomen aged 40-50 years old in the village awu-awu, Ngombol, Kab PurworejoMethods: This research uses experimental methods to do intervention form of counseling on reproductive health.Total population 54 women aged 40-50 years and all were taken as samples.Results: A positive attitude to faced menopausal women aged 40-50 years old were given counseling before andafter as many as 53.7% are educated as much as 81.5%. This is an increase of women who have a positive attitudeas much as 27.8%Conclusion: There is the influence of education on reproductive health to the attitude of facing menopause inwomen aged 40-50 years old.Keywords: Education, Attitude, Menopause